(untitled) - Kenneth C Torres (New York, 1989)
This book provides the novice in the plant tissue culture field with concise, easy-to-follow information on setting up a plant tissue culture laboratory and describes procedures for conducting experiments. It enables readers with only minimal technical knowledge to gain a practical comprehension of such topics á lab set-up, basic tissue culture techniques, nutrition and media preparation, stages of micropropagation, and micropropagation of specific horticultural crops
Keywords: horticultural crops - propagation - in vitro,plant tissue culture